2015
DOI: 10.1016/j.cellsig.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA therapy against carbohydrate sulfotransferase 15 inhibits cardiac remodeling in rats with dilated cardiomyopathy

Abstract: Carbohydrate sulfotransferase 15 (CHST15) is a sulfotransferase responsible for biosynthesis of chondroitin sulfate E (CS-E), which plays important roles in numerous biological events such as biosynthesis of proinflammatory cytokines. However, the effects of CHST15 siRNA in rats with chronic heart failure (CHF) after experimental autoimmune myocarditis (EAM) have not yet been investigated. CHF was elicited in Lewis rats by immunization with cardiac myosin, and after immunization, the rats were divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…CHST15 is responsible for bone marrow-derived mast cell and pulmonary metastasis 10, 11, 12. The effect of CHST15 siRNA on fibrosis was reported in rats with dilated cardiomyopathy 13 and in murine colitis models 14 . Furthermore, CHST15 siRNA repressed colonic fibrosis and enhanced mucosal healing in patients with Crohn disease, as shown in the safety and efficacy results of a phase 1 study reported by Suzuki et al 15 .…”
Section: Introductionmentioning
confidence: 93%
“…CHST15 is responsible for bone marrow-derived mast cell and pulmonary metastasis 10, 11, 12. The effect of CHST15 siRNA on fibrosis was reported in rats with dilated cardiomyopathy 13 and in murine colitis models 14 . Furthermore, CHST15 siRNA repressed colonic fibrosis and enhanced mucosal healing in patients with Crohn disease, as shown in the safety and efficacy results of a phase 1 study reported by Suzuki et al 15 .…”
Section: Introductionmentioning
confidence: 93%
“…Most of our current understanding comes from experiments in susceptible murine strains. Human myocarditis is mimicked in mice through infection with human coxsackie virus B3 (CVB3) or by injection of cardiac antigens that induce an autoimmune response . The latter non‐infectious models mainly provide insights into the latter phases of myocarditis.…”
Section: Immune Activation In Different Heart Failure Aetiologiesmentioning
confidence: 99%
“…All of these are involved in fibrogenesis and therefore characterize CHST15 and/or CS-E axis as a “fine-tuner” of local fibrosis. We have recently shown that blockade of CHST15 by siRNA repressed cardiac fibrosis in rats with dilated cardiomyopathy through suppressing multiple mediators associated with cardiac remodeling such as interleukin (IL)-1ß, IL-6, monocyte chemoattractant protein (MCP)-1/CCL2, collagen type 1 and 3, MMP-2, MMP-9, connective tissue growth factor (CTGF), TGF-ß and TGF-ß activated kinase (TAK)-1 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%